STRUKTUR TATAK MAMURO PADA MASYARAKAT PAKPAK DI KABUPATEN PAKPAK BHARAT - Morris Kembaren (Gesture: Jurnal Seni Tari, 2016)
This study discusses, Structure mamuro community in Pakpak Bharat Pakpak. The population in this study isin the Village Peoples Pakpak Pardomuan District of Bharat Pakpak kingdom, artist, custom dean or figures,and dancers who know the neighbor dance tradition Pakpak especially Tatak MamuroTheoretical foundation used in this research is the theory of the structure of Martin and Pesover in the bookAnya Peterson Royce, judging from the shape and morphology of dance.Data analysis techniques used in this research is descriptive qualitative, are interpreted and formulated betweenthe data with each other data so that data is accurate and carefully, in accordance with the form of datacollected through interviews, observation, documentation and literature study.Based on the results of research conducted, then Mamoru There is a dance that illustrates how the fields thatrepel birds to be harvested rice is not eaten by birds. It is known that farming for society Pakpak is onelivelihood to survive. Mamuro Tatak structure has the form of four varieties (1) pulling the rope (kinarik tinali)(2) establish new rice bind (a new page ipencer italy) (3) hunting (merburu) (4) applause (applause). The musicused in Tatak Mamuro is Pantar Cross with the instruments used are: gung, kalondang, lobat, harp, andclothing dipake in Tatak Mamuro is customary fashion Pakpak Dairi and using catapults property. In thestructure of Tatak Mamuro there are three stages: The first stage is a salutation (njuah-juah), the second stageis the content that describes repel birds (Mamuro), and the third stage is as regards cover. Tatak this Mamuroordinary dipagelarkan as a means of entertainment on society Pakpak people party or (Njuah-juah).